The Prehistory of Peronism in Santiago del Estero. Laborism, Radicalism and “política criolla” in 1946 elections (Quinto Sol, 2013)
This paper deals with the circumstances and alternatives upon which the different alliances that drove Perón to the government in 1946 elections were arranged, from the particular case of Santiago del Estero province (Argentina). Diverging from the regions where industry development had generated a strong and crowded union movement to negotiate with, previously to the election weeks, in Santiago, in hectic negotiations with a “political criolla” style, the conservative leaders, first “radicales” and then “peronistas” take the movement possession.
Keywords: Peronism; Santiago del Estero; laborism; political history